Improving Clean and Healthy Living Behavior Through Project Based Learning (Sorting Waste) in Group B Children of Pembina Mambi Kindergarten, Mamasa Regency - Martuty, Arie; Latief, Fadhilah; Hasna; Tahirah, Ilmi (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This research is a classroom action research (CAR) that aims to improve children's clean and healthy living behavior (PHBS) through the implementation of project learning (sorting waste). The research subjects were 20 children in group B of Pembina Mambi Kindergarten, Mamasa Regency. The research was conducted from May to June 2023 and was carried out in two cycles, each cycle consisting of planning, action implementation, observation, and reflection stages. Each cycle was carried out in three meetings with PHBS indicators including washing hands, sorting waste, and making crafts from waste, according to the Indonesian Ministry of Education and Culture Regulation Number 146 of 2014. The results showed that in Cycle I the average achievement of children's PHBS was 46.62% with the category of Starting to Develop (MB), so it did not meet the success criteria. After learning improvements were made in Cycle II, the average achievement increased to 75.93% with the category of Developing According to Expectations (BSH), consisting of 55% of children in the BSH category and 45% of children in the category of Developing Very Well (BSB). Thus, it can be concluded that the implementation of waste sorting project learning is effective in improving children's clean and healthy living behavior in the school environment.